Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Vũ Phan Hữu Phúc
Xem chi tiết
Tiên Võ
Xem chi tiết
Nguyễn Lê Phước Thịnh
15 tháng 10 2021 lúc 23:12

Bài 2: 

a: \(x^2+5x-6=\left(x+6\right)\left(x-1\right)\)

b: \(5x^2+5xy-x-y\)

\(=5x\left(x+y\right)-\left(x+y\right)\)

\(=\left(x+y\right)\left(5x-1\right)\)

c:\(-6x^2+7x-2\)

\(=-6x^2+3x+4x-2\)

\(=-3x\left(2x-1\right)+2\left(2x-1\right)\)

\(=\left(2x-1\right)\left(-3x+2\right)\)

Lấp La Lấp Lánh
15 tháng 10 2021 lúc 23:18

1.

a) \(=x^2\left(x^2+2x+1\right)=x^2\left(x+1\right)^2\)

b) \(=\left(x+y\right)^3-\left(x+y\right)=\left(x+y\right)\left[\left(x+y\right)^2-1\right]\)

\(=\left(x+y\right)\left(x+y-1\right)\left(x+y+1\right)\)

c) \(=5\left[\left(x^2-2xy+y^2\right)-4z^2\right]=5\left[\left(x-y\right)^2-4z^2\right]\)

\(=5\left(x-y-2z\right)\left(x-y+2z\right)\)

2.

a) \(=x\left(x+2\right)+3\left(x+2\right)=\left(x+2\right)\left(x+3\right)\)

b) \(=5x\left(x+y\right)-\left(x+y\right)=\left(x+y\right)\left(5x-1\right)\)

c) \(=-\left[3x\left(2x-1\right)-2\left(2x-1\right)\right]=-\left(2x-1\right)\left(3x-2\right)\)

3.

b) \(=2x\left(x-1\right)+5\left(x-1\right)=\left(x-1\right)\left(2x+5\right)\)

c) \(=-\left[5x\left(x-3\right)-1\left(x-3\right)\right]=-\left(x-3\right)\left(5x-1\right)\)

4.

a) \(\Rightarrow\left(x-1\right)\left(5x-1\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x=1\\x=\dfrac{1}{5}\end{matrix}\right.\)

b) \(\Rightarrow2\left(x+5\right)-x\left(x+5\right)=0\)

\(\Rightarrow\left(x+5\right)\left(2-x\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x=-5\\x=2\end{matrix}\right.\)

Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
5 tháng 6 2017 lúc 4:56

x 2  – 9 =  x 2  – 3 2  = (x + 3)(x – 3)

Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
10 tháng 10 2018 lúc 9:51

Ta có:  x 2 - 7 =  x 2  - 7 2  = (x + 7 )(x -  7  )

Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
11 tháng 12 2019 lúc 6:44

x2 - 6 = x2 - (√6)2 = (x - √6)(x + √6)

Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
13 tháng 11 2017 lúc 14:10

 x2 - 3 = x2 - (√3)2 = (x - √3)(x + √3)

Cíuuuuuuuuuu
Xem chi tiết
Trần Ái Linh
18 tháng 7 2021 lúc 18:07

`x^2+2x-5`

`=(x^2+2x+1)-6`

`=(x+1)^2-\sqrt6^2`

`=(x+1+\sqrt6)(x+1-\sqrt6)`

Vinh Phú Phạm
18 tháng 7 2021 lúc 18:26

\(x^2+2x-5\)

\(= x^2+2x+1-6\)

\(= (x+1)^2-6\)

\(= (x+1)^2-\left(\sqrt{6}\right)^2\)

\(= \left(x+1-\sqrt{6}\right)\left(x+1+\sqrt{6}\right)\)

Nguyễn Lê Phước Thịnh
18 tháng 7 2021 lúc 20:23

\(x^2+2x-5\)

\(=x^2+2x+1-6\)

\(=\left(x+1\right)^2-6\)

\(=\left(x+1-\sqrt{6}\right)\left(x+1+\sqrt{6}\right)\)

Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
29 tháng 3 2019 lúc 12:37

6x – 9 –  x 2  = - ( x 2  – 2.x.3 + 3 2 ) = - x - 3 2

Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
7 tháng 6 2017 lúc 11:27

4 x 2  – 25 = 2 x 2  – 5 2  = (2x + 5)(2x – 5)

Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
9 tháng 5 2019 lúc 5:40

Ta có:  x 2 - 2 2 x + 2 = x 2 - 2 . x . 2 + 2 2 = x - 2 2